2005
DOI: 10.1186/1471-2164-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in the brain and kidney of rainbow trout in response to handling stress

Abstract: Background: Microarray technologies are rapidly becoming available for new species including teleost fishes. We constructed a rainbow trout cDNA microarray targeted at the identification of genes which are differentially expressed in response to environmental stressors. This platform included clones from normalized and subtracted libraries and genes selected through functional annotation. Present study focused on time-course comparisons of stress responses in the brain and kidney and the identification of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 32 publications
4
85
0
2
Order By: Relevance
“…Both head-kidney and spleen contain a high number of macrophages [28], suggesting that MC2R activation could be involved in the modulation of the sea bass immune system, as previously proposed [29]. Microarray studies have demonstrated the effects of handling stress on the expression of immune system-related genes in fish [30]. In addition, ACTH has been shown to modulate cytokine expression in the gilthead seabream ( Sparus autara , [31]).…”
Section: Discussionmentioning
confidence: 64%
“…Both head-kidney and spleen contain a high number of macrophages [28], suggesting that MC2R activation could be involved in the modulation of the sea bass immune system, as previously proposed [29]. Microarray studies have demonstrated the effects of handling stress on the expression of immune system-related genes in fish [30]. In addition, ACTH has been shown to modulate cytokine expression in the gilthead seabream ( Sparus autara , [31]).…”
Section: Discussionmentioning
confidence: 64%
“…Small changes in gene expression have previously been shown to be of physiological relevance, as in the case of precocious sexual maturation in the brains of salmon [57]. In the case of handling stress on trout, it has been found that the majority of stress-response genes exhibit small or moderate changes in expression [58]. Acquired thermal tolerance via preconditioning may be a case of physiological fine-tuning on the part of the host, not massive transcriptional changes of large magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Examples exist in rainbow trout [95] gilthead sea bream [96], European sea bass [97], Atlantic salmon ( Salmo salar ) [98], common carp ( Cyprinus carpio ) [99] or Senegalese sole ( Solea senegalensis ) [26], but also in the turbot [37]. In the present study, samples from the reproductive and immune tissues were used to characterize their transcriptome using different sequencing strategies and de novo assembly to identify a large number of genes previously unknown in turbot.…”
Section: Resultsmentioning
confidence: 99%